Comparisonal Analysis Of Financial Performance In Sharia Banking Before And During The Pandemic (Case Study Of Pt. Bank Sulselbar - Muttalib, Abdul; Madjid, St. Saleha; Jusmita, Leli (Jurnal Ar-Ribh, 2022)
The purpose of this study to find out how the financial performance of PT. Bank Sulselbar KC Syariah Makassar based on a value added and profit and loss approach. This research is a type of quantitative research with a comparative descriptive approach. The data used in this research is secondary data. The data source is in the form of financial ratios in the annual financial statements of South Sulawesi KC Syariah Makassar for the 2019-2020 period. The results of this study indicate that the financial performance of PT. Bank Sulselbar KC Syariah Makassar Year 2019-2020 which is calculated using the added value approach produces a larger ratio value when compared to using the profit and loss approach.